2012
DOI: 10.1051/mmnp/20127313
|View full text |Cite
|
Sign up to set email alerts
|

Memory Effects in Population Dynamics : Spread of Infectious Disease as a Case Study

Abstract: Abstract. Modification of behaviour in response to changes in the environment or ambient conditions, based on memory, is typical of the human and, possibly, many animal species.One obvious example of such adaptivity is, for instance, switching to a safer behaviour when in danger, from either a predator or an infectious disease. In human society such switching to safe behaviour is particularly apparent during epidemics. Mathematically, such changes of behaviour in response to changes in the ambient conditions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 72 publications
0
35
0
7
Order By: Relevance
“…A dinâmica das populações entre os compartimentos fica mais bem apresentada no diagrama abaixo, figura (1): (PIMENOV et al, 2012). Esta memória imunológicaé uma capacidade do sistema imune adaptativo responsável por propiciar respostas mais eficientes e rápidasà ocorrência de exposiçãoà antígenos encontrados previamente, seja na forma de exposição natural, ou na forma de vacinas.…”
Section: Modelo Compartimental Sircunclassified
“…A dinâmica das populações entre os compartimentos fica mais bem apresentada no diagrama abaixo, figura (1): (PIMENOV et al, 2012). Esta memória imunológicaé uma capacidade do sistema imune adaptativo responsável por propiciar respostas mais eficientes e rápidasà ocorrência de exposiçãoà antígenos encontrados previamente, seja na forma de exposição natural, ou na forma de vacinas.…”
Section: Modelo Compartimental Sircunclassified
“…The resulting model is a reaction-diffusion system including, as reaction terms, discontinuous hysteresis relay operators and the integral of those. This integral can be interpreted as the Preisach operator [8,13,31,32,34,35,43,44,46,50] with a time dependent density (the density is a component of the solution describing the varying distribution of bacteria). In [23], we have shown that fitness, competition and diffusion can act together to select a nontrivial distribution of phenotypes (states) over the population of thresholds.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In [13], a system of fractional differential equations is used to study the effect of memory on epidemic evolution. In [10], the hysteresis effect is used to model biological phenomena that activate defense mechanisms of certain living beings. For example, in a situation of spreading of an infectious disease for human beings, depending on type of disease, previous experiences can reveal that social distance or additional hygiene habits are defensive behaviors to prevent its propagation.…”
Section: Introductionmentioning
confidence: 99%